Customer Decision to Save in Sharia Banks Following A Ransomware Attack: An Analysis of the Role of Word of Mouth, Trust, Perception of Cybersecurity, and Perception of Sharia Label - Sudana, Sudana; Marlina, Lina (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2024)
Ransomware attacks on Islamic banking institutions can lead to a decline in public interest in saving. To stimulate the growth of savings, it is crucial to investigate the determinants influencing customer decision to save their money in Islamic banking institutions following a ransomware attack. This study implemented a unique approach in examining the impact of perceptions of cybersecurity and Sharia label on the decision to save in Sharia banks in Indonesia subsequent to a ransomware attack. It aims to explore the intervening role of trust and Word of Mouth (WOM) in information dissemination and analyze how the Sharia label can mitigate the risk of customer attrition, thereby maintaining the level of customer trust. This study employed a quantitative causal method, specifically a path analysis model. Data were collected through questionnaires sent to customers of Sharia banks in Indonesia selected using a probability sampling technique. The Structural Equation Model (SEM) with a Partial Least Squares (PLS) approach was utilized for analysis. The findings emphasize the significance of cybersecurity, Sharia label, and WoM in understanding customer decision to save in Sharia banks. This study thus offers valuable insights for Sharia banks, identifying areas in need of improvements in security and marketing policies and enabling more proactive strategies to ensure customer trust and enhance performance in facing growing challenges.